CARACTERIZAÇÃO DA ISOCITRATO LIASE E METILISOCITRATO LIASE DO FUNGO PATOGÊNICO HUMANO Paracoccidioides brasiliensis - TROIAN, Rogério Fraga (2009)
Paracoccidioides brasiliensis, a thermodimorphic fungus, is the causative agent of paracoccidioidomycosis (PCM), a prevalent systemic mycosis in Latin America. Pathogenicity appears to be intimately related to the dimorphic transition from the hyphal to the yeast form, which is induced by a shift from environmental temperature to the temperature of the mammalian host. To cope with nutrient deprivation during the infection process, a number of pathogens employ the glyoxylate cycle (GC) to utilize fatty acids as carbon sources. The genes which constitute this pathway have been implicated in pathogenesis. An important aspect in the interaction between P.brasiliensis and your host is the ability to adhere to matrix extracelular components. In this work has shown that the isocitrate lyase of P. brasiliensis (PbICL) is located in the cell wall and also in the cytoplasm. PbICL recombinant and polyclonal antibody were able to inhibit the interaction of P. brasiliensis to epithelial cell cultures in vitro. Was also evaluated the ability of PbICL recombinant to connect the components of the extracellular matrix such as laminin, fibronectin, collagen type I and IV. These results suggest that PbICL is necessary to interaction between molecules of the extracellular matrix and P.brasiliensis, and that this interaction is crucial in adhesion and invasion of the fungus to the host cells. The kinetic parameters of PbICLr were determined. The sequence coding for methylisocitrate lyase of P. brasiliensis (PbmeICL) and the recombinant protein PbmeICLr were obtained.